Tratado de estudios organizacionales. - Clegg, Stewart; Ramírez Martínez, Guillermo; Gonzales-Miranda, Diego René (Colección Académica (Medellín, Colombia), 2017)
This handbook provides an overview of the current state of the discipline and its future possibilities. Presenting a balance between the established mainstream and newer concerns and approaches, it reflects the diversity and dynamism of the field.